Efektifitas Strategi Pembelajaran Question Student Have Terhadap Hasil Belajar Siswa Dalam Mata Pelajaran Sejarah Kebudayaan Islam Kelas VIII Mts Thawalib Gunung Padang Panjang - Ayu Citra Dewi; Zulfikri; Taufik Rahman; Afifah Fitriah (SURAU : Journal of Islamic Education, 2024)
Abstract This study aims to find out the impact of Application of Learning Strategy Question Student Have on Students' Learning Results in Islamic Culture History Lectures Class Viii Mts Thawalib Gunung Padang Long. This research is an experimental study with the design of Posttest Only Control Design. The population in this study is class VIII MTs Thawalib Long Field Mountain. The researchers selected samples with purposive sampling from a particular population. The researchers chose class VIII A as the experimental class and class VIII B as the control class. The instruments used are tests and to test research hypotheses, researchers use Test-t and data processing using SPSS. The results of this study show that the learning outcomes of students taught with the Question Student Have learning strategy are higher than the learning strategy of discussion. Students in the experimental class are better at learning than in the control class, class VIII A with an average of 80,72, and control class VIII B with a average of 67,47. The result is bigger than the table. The table is 3.021 and the table is 1.681. So the application of the learning strategy Question Student Have has been effective against the learning results of students on the subject of Islamic Cultural History Class VIII Mts Thawalib Gunung Padang Long.   Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh Penerapan Strategi Pembelajaran Question Student Have Terhadap Hasil Belajar Siswa Dalam Mata Pelajaran Sejarah Kebudayaan Islam Kelas Viii Mts Thawalib Gunung Padang Panjang. Penelitian ini merupakan penelitian eksperimen dengan desain Posttest Only Control Design. Populasi dalam penelitian ini adalah kelas VIII MTs Thawalib Gunung Padang Panjang. Peneliti memilih sampel dengan purposive sampling dari populasi tertentu. Peneliti memilih kelas VIII A sebagai kelas eksperimen dan VIII B sebagai kelas kontrol. Instrumen yang digunakan adalah tes dan untuk menguji hipotesis penelitian, peneliti menggunakan Uji-t dan pengolahan data menggunakan SPSS. Hasil penelitian ini menunjukkan bahwa hasil belajar siswa yang diajar dengan strategi pembelajaran Question Student Have lebih tinggi daripada strategi pembelajaran diskusi. Hal ini diketahui dari nilai hasil instrumen supervisi pelaksanaan pembelajaran sebesar 84,68%. Hasil belajar siswa kelas eksperimen lebih baik dari pada kelas kontrol, kelas VIII A dengan rata-rata 80,72, dan kelas kontrol VIII B dengan rata-rata 67,47. Hasil thitung lebih besar dari pada ttabel. thitung sebesar 3.021 dan ttabel sebesar 1.681. Sehingga penerapan strategi pembelajaran Question Student Have telah efektif terhadap hasil belajar siswa pada mata pelajaran Sejarah Kebudayaan Islam Kelas VIII Mts Thawalib Gunung Padang Panjang.